2021
DOI: 10.1016/j.mtbio.2021.100124
|View full text |Cite
|
Sign up to set email alerts
|

Reactive-oxygen-species-scavenging nanomaterials for resolving inflammation

Abstract: Reactive oxygen species (ROS) mediate multiple physiological functions; however, the over-accumulation of ROS causes premature aging and/or death and is associated with various inflammatory conditions. Nevertheless, there are limited clinical treatment options that are currently available. The good news is that owing to the considerable advances in nanoscience, multiple types of nanomaterials with unique ROS-scavenging abilities that influence the temporospatial dynamic behaviors of ROS in biological systems h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 145 publications
0
61
0
Order By: Relevance
“…The road ahead is full of thorns, but it is a considerable deal if nanodrug harnessing RONS and inflammation achieve success in the control of liver injury, which further promote the progress of most nanodrugs. The success of some nanodrugs has set a precedent [ 155 ], and four main challenges should be considered seriously learned from previous experiences [ 308 , 309 ] ( Fig. 18 ), which is benefit for the meaningful clinical translation of nanodrug harnessing RONS and inflammation for liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…The road ahead is full of thorns, but it is a considerable deal if nanodrug harnessing RONS and inflammation achieve success in the control of liver injury, which further promote the progress of most nanodrugs. The success of some nanodrugs has set a precedent [ 155 ], and four main challenges should be considered seriously learned from previous experiences [ 308 , 309 ] ( Fig. 18 ), which is benefit for the meaningful clinical translation of nanodrug harnessing RONS and inflammation for liver disease.…”
Section: Discussionmentioning
confidence: 99%
“… 333 Additional research evidence has shown that nano-antioxidants have the excellent antioxidant capacity and superior tolerance to harsh microenvironments in comparison to their natural counterparts. 334 Besides, the role of mitochondrial dysfunction in vascular aging encourages the exploration of mitochondrial-targeted therapeutic modalities for the prevention and intervention of vascular aging-related diseases. Moreover, mitochondria-targeting nanoparticles for the treatment of vascular aging-related diseases have attracted considerable research attention.…”
Section: Nanoparticle-based Therapeutic Methods For Vascular Aging-re...mentioning
confidence: 99%
“…Prolonged inhalation of TiO 2 causes its deposition in the lung, which leads to ROS generation (considered as a KE) and oxidative stress (considered as another KE) in lung adenomas/carcinomas ( Braakhuis et al, 2021 ). While nanomaterials potentially induce ROS ( Jacobsen et al, 2008 ) and oxidative stress ( Halappanavar et al, 2021 ), nanoparticle (NP)-based ROS-scavenging approaches have also emerged as nanomedicines for anti-inflammatory treatments ( Huang et al, 2021 ). These ROS-scavenging NPs include catalytic NPs that have SOD-, CAT-, POD-, and glutathione-like enzyme activities, free-radical trapper NPs such as fullerene that captures ROS via conjugated double bonds, 2, 2, 6, 6-tetramethylpiperidinenoxyl (TEMPO) that captures ROS via the single electron on nitroxide, and redox ROS-scavenging NPs such as curcumin or bilirubin NPs ( Nash and Ahmed, 2015 ; Huang et al, 2021 ).…”
Section: Relationships Between Ros and Pathogenesismentioning
confidence: 99%
“…While nanomaterials potentially induce ROS ( Jacobsen et al, 2008 ) and oxidative stress ( Halappanavar et al, 2021 ), nanoparticle (NP)-based ROS-scavenging approaches have also emerged as nanomedicines for anti-inflammatory treatments ( Huang et al, 2021 ). These ROS-scavenging NPs include catalytic NPs that have SOD-, CAT-, POD-, and glutathione-like enzyme activities, free-radical trapper NPs such as fullerene that captures ROS via conjugated double bonds, 2, 2, 6, 6-tetramethylpiperidinenoxyl (TEMPO) that captures ROS via the single electron on nitroxide, and redox ROS-scavenging NPs such as curcumin or bilirubin NPs ( Nash and Ahmed, 2015 ; Huang et al, 2021 ). Specific ROS-targeting NPs as drug delivery systems, where solubility changes by ROS or extended-release are utilized for anti-cancer therapy, have been developed as well ( Kim et al, 2015 ).…”
Section: Relationships Between Ros and Pathogenesismentioning
confidence: 99%